Profile and views on botanical literacy: A study from a final year preservice biology teacher - Dita Purwinda Anggrella; Ahmad Kamal Sudrajat (University of Muhammadiyah Malang, 2025)
Botanical literacy is an important competency preservice biology teachers must have to support contextual and sustainability-oriented science learning. This study aims to describe the profile and views of botanical literacy of preservice biology teacher students in their final year of study. The study was conducted at one of the state Islamic universities in Central Java, involving 33 students who had completed all pedagogical and biological science courses. The approach used in this study was mixed methods with an explanatory design. The type of research used was a survey. Data collection began with a test to measure students' botanical literacy skills and a validated questionnaire to explore their views on the importance of botanical literacy and how they would teach it as teachers. Furthermore, semi-structured interviews were conducted to obtain in-depth information about preservice biology teacher students' views on botanical literacy. The results showed that students had good results in the indicators of reading graphs and concluding based on data but were weak in the indicators of evaluating the validity of sources and recognising valid scientific arguments. In addition, students showed positive views on the importance of botanical literacy in increasing ecological awareness and the role of teachers in building students' awareness of botanical literacy. The results of this study indicate that it is important to develop biological literacy, especially botany, of preservice teacher students, considering that Indonesia has high plant diversity.